2017
DOI: 10.1080/13691058.2017.1309070
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional harassment and deviant embodiment among Autistic adults: (dis)ability, gender and sexuality

Abstract: Harassment scholarship increasingly attends to the intersectional nature of harassment and its function within systems of domination. However, little of this work includes disability. In-depth interviews with 24 adults on the autism spectrum in the USA demonstrate the intersections of gender, sexuality and (dis)ability in the construction of deviant embodiments as targets for harassment. These intersections also shape how participants made sense of these experiences of violence. Participants' disability charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…Adolescents express concerns about deviating from the norm, so they may worry a minority sexuality, in addition to ID, would make them too different (Löfgren-Mårtenson, 2009). The nexus between sexuality and ID is an example of intersectionality, that is, both the social differences interact and contribute to a greater level of social oppression or exclusion (Barnett, 2017). To remedy the social exclusion created by intersectionality, each axis of exclusion must be addressed (Meekosha, 2006).…”
Section: Conservative Curricula Increase Social Exclusionmentioning
confidence: 99%
“…Adolescents express concerns about deviating from the norm, so they may worry a minority sexuality, in addition to ID, would make them too different (Löfgren-Mårtenson, 2009). The nexus between sexuality and ID is an example of intersectionality, that is, both the social differences interact and contribute to a greater level of social oppression or exclusion (Barnett, 2017). To remedy the social exclusion created by intersectionality, each axis of exclusion must be addressed (Meekosha, 2006).…”
Section: Conservative Curricula Increase Social Exclusionmentioning
confidence: 99%
“…40 Furthermore, people with disabilities may become targets of gendered harassment because of misunderstandings that stem from differences in their behavior and comportment, which Jessica Barnett suggests are read through the lens of gender nonconformity. 41 Then again, the pervasiveness of normalized expectations of bodily comportment, and ableist ignorance of bodily, cognitive, and behavioral differences, can lead to misunderstandings of a different sort, in which certain actions by people with disabilities are (mis)read as harassing behavior. Addressing gendered harassment of individuals with disability labels would therefore need to attend to the ways that heteropatriarchal structures intertwine with entrenched ableism to situate "abnormalcy" as a predictor of vulnerability.…”
Section: Georgementioning
confidence: 99%
“…Barnett's 2017 smaller study of adults on the autism spectrum in the United States found that harassment of people on the autism spectrum often relied on gendered assumptions and that the "conflation of disability, gender and sexuality" determined who was targeted for harassment (Barnett 2017(Barnett , p. 1216. For example, people in this group were less able, because of their autistic traits, to correctly "perform" gender roles, which left them exposed to harassment.…”
Section: Sexual Harassment Of Women With Behavioural and Personality mentioning
confidence: 99%
“…For example, people in this group were less able, because of their autistic traits, to correctly "perform" gender roles, which left them exposed to harassment. The author concluded that harassment that appeared "sexual" had hidden ableist impacts: "harassment that is nominally gender and/or sexuality based often targets impairment effects, acting as a mechanism of social disablement" (Barnett 2017(Barnett , p. 1220. As with the Shaw, Chan and McMahon study above, Barnett suggests that behavioural impairments make people particular targets of harassment: "deviation of comportment is more closely policed than deviation of physical functioning" (Barnett 2017(Barnett , p. 1212.…”
Section: Sexual Harassment Of Women With Behavioural and Personality mentioning
confidence: 99%
See 1 more Smart Citation